The contribution and significance of product strategy towards consumer acceptance: a case study of JKING Sdn. Bhd. in Johor Bahru / Mohammad Norazham Ismail - Ismail, Mohammad Norazham (Faculty of Business and Management, 2006)
The purpose of this research is to study the contribution and significance of product strategy towards consumer acceptance: A case study of JKING Sdn. Bhd. in Johor Bahru. This study also wants to analyze the relationships between design and consumer acceptance, to identify the relationships between quality and consumer acceptance and to understand the relationships between price and consumer acceptance. Moreover, this study will examine the significance relationship between design and consumer acceptance, the significance relationship between quality and consumer acceptance, and significance relationship between price and consumer acceptance.